Gold mineralization and metallogenesis associated with mantle dynamics in East China - He, Chuansong (Frontiers in Earth Science, 2022)
East China can be divided into two parts: the North China Block (or North China Craton) (NCC) and the South China Block (SCB). The mechanism for the destruction of the NCC and the large-scale magmatic activity in the SCB during the Mesozoic is a major focus in the geosciences; however, related scientific issues, such as gold mineralization in the NCC and the metallogenesis in the SCB, remain enigmatic. Recently, receiver function analysis and tomography have been used to define the vestiges of an upwelling mantle plume beneath the NCC and large-scale mantle upwelling beneath the SCB in the Mesozoic, which may be related to gold mineralization and metallogenesis in this area. In this study, the dynamic processes of the mantle plume and upwelling mantle are analysed, and the relationships between the mantle plume and gold mineralization as well as between mantle upwelling and metallogenesis are discussed. Finally, it is suggested that gold mineralization in the NCC might be linked to a Mesozoic mantle plume while metallogenesis in the SCB might be related to Mesozoic mantle upwelling.